Immunomodulatory effects of atorvastatin on peripheral blood mononuclear cells infected with Mycobacterium tuberculosis - Sabeel, Solima; Motaung, Bongani; Ozturk, Mumin; Mafu, Trevor S.; Wilkinson, Robert J.; Thienemann, Friedrich; Guler, Reto (Frontiers in Immunology, 2025)
BackgroundTuberculosis (TB) remains a major global health threat, contributing substantially to high morbidity and mortality rates. This underscores the urgent need for more effective interventions. Recent studies highlight the potential of host-directed therapy approaches to enhance immune defences against TB. Atorvastatin, recognized for both its lipid-lowering properties and its immunomodulatory effects, has emerged as a compelling candidate for host-directed therapy against TB. Here, we investigated the ex vivo efficacy of atorvastatin in inducing immunomodulatory activities (phagosome maturation, autophagy, and apoptosis) and enhancing the mycobacterial killing capacity in Mycobacterium tuberculosis (Mtb)-infected peripheral blood mononuclear cells (PBMCs).MethodBlood samples from healthy donors were collected for PBMC isolation. PBMCs were then treated overnight with or without atorvastatin, followed by infection with Mtb strains (H37Rv, HN878, and CDC1551) to evaluate intracellular mycobacterial growth by colony-forming units enumeration. Furthermore, co-localization of late endosomal marker (Rab-7), lysosomal markers (Cathepsin-D and LAMP-3), and autophagy marker (LC3B) with GFP-Mtb was investigated in infected PBMCs using laser scanning confocal microscopy. Moreover, multiple apoptotic assays were performed, including the TUNEL assay for DNA fragmentation, quantification of caspase-3 activity, and the expression levels of the pro-apoptotic gene (Bax) and anti-apoptotic gene (Bcl2).ResultsTreatment with atorvastatin significantly reduced intracellular mycobacterial replication compared to untreated controls in Mtb-infected PBMCs. Moreover, atorvastatin enhanced co-localization between Mtb and late endosomal marker (Rab-7), lysosomal markers (Cathepsin-D and LAMP-3), and autophagy marker (LC3B) in Mtb-infected PBMCs. Furthermore, atorvastatin robustly promoted apoptosis in Mtb-infected PBMCs, as demonstrated by TUNEL assay and caspase-3 activation.ConclusionOur findings highlight atorvastatin’s potential as a crucial modulator of the immune response in Mtb-infected PBMCs, supporting its role in host-directed therapy.